Cross Layer Design for Multimedia Transmission over Wireless Networks - Christos Bouras; Apostolos Gkamas; G Kioumourtzis (Next Generation Mobile Networks and Ubiquitous Computing, 2010)
Over the last years a number of new protocols have been developed for multimedia applications in the whole OSI layer?s scale. In addition wireless communications and networking fast occupy centre stage in research and development activity in the area of communication networks. In order to support better wireless user the cross layer design paradigm has been proposed. This chapter presents the challenges in design and implementation of cross layer adaptation schemes for multimedia transmission over wireless networks. In addition this chapter presents the most important parameters and constrains that should be taken into consideration when attempting cross layer adaptation in wireless networks that involves different protocols in the overall protocol stack.